Sepsis Electronic Decision Support Screen in High-Risk Patients Across Age Groups in a Pediatric Emergency Department. Issue 8 (5th August 2022) - Witting, Celeste S.; Simon, Norma-Jean E.; Lorenz, Doug; Murphy, Julia S.; Nelson, Jill; Lehnig, Katherine; Alpern, Elizabeth R.
Abstract : Objective: This study aimed to compare the performance of a pediatric decision support algorithm to detect severe sepsis between high-risk pediatric and adult patients in a pediatric emergency department (PED). Methods: This is a retrospective cohort study of patients presenting from March 2017 to February 2018 to a tertiary care PED. Patients were identified as high risk for sepsis based on a priori defined criteria and were considered adult if 18 years or older. The 2-step decision support algorithm consists of (1) an electronic health record best-practice alert (BPA) with age-adjusted vital sign ranges, and (2) physician screen. The difference in test characteristics of the intervention for the detection of severe sepsis between pediatric and adult patients was assessed at 0.05 statistical significance. Results: The 2358 enrolled subjects included 2125 children (90.1%) and 233 adults (9.9%). The median ages for children and adults were 3.8 (interquartile range, 1.2–8.6) and 20.1 (interquartile range, 18.2–22.0) years, respectively. In adults, compared with children, the BPA alone had significantly higher sensitivity (0.83 [95% confidence interval CI, 0.74–0.89] vs 0.72 [95% CI, 0.69–0.75]; P = 0.02) and lower specificity (0.11 [95% CI, 0.07–0.19] vs 0.48 [95% CI, 0.45–0.51; P < 0.001). With the addition of provider screen, sensitivity and specificity were comparable across age groups, with a lower negative predictive value in adults compared with children (0.66 [95% CI, 0.58–0.74] vs 0.77 [95% CI, 0.75–0.79]; P = 0.005). Conclusions: The BPA was less specific in adults compared with children. With the addition of provider screen, specificity improved; however, the lower negative predictive value suggests that providers may be less likely to suspect sepsis even after automated screen in adult patients. This study invites further research aimed at improving screening algorithms, particularly across the diverse age spectrum presenting to a PED.